Conditions for religious institute admissions - DOMASZK, ARKADIUSZ (Prawo Kanoniczne, 2017)
The religious institutes in the Catholic Church priorities the issue of the formation of candidates. Vocation to a religious life is verified at the initial stages: in prenovitiate and novitiate. This article mentioned the canonical and legal requirements determining validity and honesty of the admission, first to a postulant and then to a novitiate. A decision concerning the admission of candidates is made by higher superiors. Guidelines in making the decisions are provided by recognition of age, health, personality and maturity of the interested. Subsequently, the superiors must exclude the existence of any obstacles which would cause nullity of the legal transaction: admission to novitiate. Their decision is based on prior familiarization with documents and certificates which are demanded or required by the common law of the Church and own law of a religious institute. They should also consider prohibitions concerning novitiate admissions since although they do not cancel the decision, ignoring them would be an ill deed. The actions of superiors, taken meticulously and in accordance with the Canon Law, will result in good discrimination and admission of appropriate and suitable candidates, and that, eventually, will prove favorable to the latter and the institute itself.